(untitled) - Vrábelová, Lucia; Kremeňová, Iveta (Doprava a spoje, 2006)
This paper deals with financial derivate's pricing, especially lookback option's pricing, using the Binomial Tree Model. The price of European lookback option calculated from Binomial Tree model is compared with the price of the same American lookback option calculated from Binomial Model.